Correlation Analysis of Hemoglobin-to-Red Blood Cell Distribution Width Ratio and Frailty in Elderly Patients With Coronary Heart Disease - Qu, Jiling; Zhou, Ting; Xue, Mengxin; Sun, Huiping; Shen, Yijing; Chen, Yuhui; Tang, Lei; Qian, Lin; You, Jiachun; Yang, Ruohan; Liu, Yongbing (Frontiers in Cardiovascular Medicine, 2021)
Abstract: Background: Coronary heart disease (CHD) is a common chronic disease in the elderly. Frailty can accelerate the development of CHD and lead to adverse health outcomes. Risk prediction and decision-making for frailty are crucial. The peripheral hemoglobin-to-red blood cell distribution width ratio (HRR) is a novel biomarker of inflammation. Our purpose was to explore the correlation between HRR and frailty in elderly patients with CHD. Methods: This cross-sectional study evaluated 245 Chinese hospitalized patients with CHD. Blood parameters measured upon admission were obtained via the hospital electronic information medical record system. The Fried Frailty Phenotype Scale was used to evaluate the frailty status of the participants. The Receiver operating characteristic curve was used to determine the optimal cut-off values of HRR. We used univariate analysis to examine the potential factors affecting frailty. Kendall's tau-b grade correlation was used to analyze the correlation between HRR and frailty. The ordered logistic regression model was used to analyze the relationship between HRR and frailty. Results: A total of 233 elderly patients with CHD were included in our study. Among the patients, 33.48% (78) were in a state of frailty. The optimal cut-off values of HRR was 9.76. The area under the curve (AUC) for HRR in the frailty patients was 0.652, exceed Hb (AUC = 0.618) and RDW (AUC = 0.650). Kendall's tau-b grade correlation analysis showed that HRR (K = -0.296, P < 0.001) was negatively correlated with frailty. The ordered logistic regression analysis determined that lower HRR was associated with frailty (P < 0.05) after adjusted for age, body mass index, number of drugs, comorbidity index, heart failure, red blood cells, albumin, total cholesterol, triglyceride, high density lipoprotein cholesterol and low density lipoprotein cholesterol. Conclusion: Lower HRR is an independent risk factor for frailty in elderly hospitalized patients with CHD. HRR was a more powerful prognostic indicator for frailty than either Hb or RDW alone. Clinicians should focus on timely identification of the risk of frailty in order to improve patient quality of life and to reduce the risk of complications.